Search for Diphoton Events with Large Missing Transverse Energy in 6.3 fb(-1) of p(p)over-bar Collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Mackin, D.; et al. (Amer Physical Soc, 2010)
We report a search for diphoton events with large missing transverse energy produced in p (p) over bar collisions at root s = 1.96 TeV. The data were collected with the D0 detector at the Fermilab Tevatron Collider and correspond to 6.3 fb(-1) of integrated luminosity. The observed missing transverse energy distribution is well described by the standard model prediction, and 95% C.L. limits are derived on two realizations of theories beyond the standard model. In a gauge-mediated supersymmetry breaking scenario, the breaking scale Lambda is excluded for Lambda < 124 TeV. In a universal extra dimension model including gravitational decays, the compactification radius R-c is excluded for R-c(-1) < 477 GeV.